2013
DOI: 10.1002/jbm.a.34976
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid‐based nanocomposite hydrogels for ocular drug delivery applications

Abstract: Hyaluronic acid (HA) is a widely investigated biomaterial for many therapeutic applications owing to its unique properties of biocompatibility, biodegradation, and viscoelasticity. HA being a natural component of eye tissue with significant role in wound healing is a natural choice as a carrier for ocular drug delivery, provided the incorporated drugs are released in a sustained manner. However, localized sustained release of drugs inside eye has been difficult to achieve because of the inability to retain car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Hydrogels are able to be utilized in conjunction with other technologies in order to improve ocular drug delivery. This can be seen in a study by Widjaja et al (2015), where a hyaluronic acid-nanocomposite hydrogel was formulated with a sample drug, latanoprost. This system, in which the modified hyaluronic acid was combined with liposomes which contained the drug before crosslinking occurred, showed longer drug release profiles than the hydrogel and liposomes each did on their own.…”
Section: Hyaluronic Acid Polymeric Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels are able to be utilized in conjunction with other technologies in order to improve ocular drug delivery. This can be seen in a study by Widjaja et al (2015), where a hyaluronic acid-nanocomposite hydrogel was formulated with a sample drug, latanoprost. This system, in which the modified hyaluronic acid was combined with liposomes which contained the drug before crosslinking occurred, showed longer drug release profiles than the hydrogel and liposomes each did on their own.…”
Section: Hyaluronic Acid Polymeric Platformsmentioning
confidence: 99%
“…The drug release mechanism is shown in Figure 5; it was found that both liposomes with entrapped drug and free drug were released from the hydrogel matrix which is what is believed to be the reason behind the sustained drug delivery profile which was observed. Although only preliminary studies were conducted; with further research, these nanocomposite systems are a potential candidate for the delivery of drugs to the eye after a single administration (Widjaja et al, 2015). Figure 5 shows how the drug is released from the system.…”
Section: Hyaluronic Acid Polymeric Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic polymers (polyvinyl alcohol, poloxamers, etc.) and polysaccharides (chitosan, hyaluronic acid, methylcellulose, carboxymethylcellulose, dextran, gellan) are frequently used to obtain ophthalmic drug delivery systems (Patel et al, 2010a;Kadajji and Betageri, 2011;Hermans et al, 2014;Widjaja et al, 2014). If these polymers are mucoadhesive, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Latanoprost acid experiences a higher penetration resistance through the lipophilic epithelium and the endothelial cells of the corneal membrane [2,15]. Despite the popularity of latanoprost in the management of glaucoma, a careful literature review revealed only handful studies reporting on the development of sustained release delivery systems [1,2,[16][17][18][19]. Most of these studies used subconjunctival injection of latanoprost liposomes, which prolonged the drug release for up to 120 days.…”
Section: Introductionmentioning
confidence: 99%